Characteristics of Alginate Extract from Padina Sp. - Susanto, Tri; Rakhmadiono, Sugeng; Mujianto, Mujianto (Jurnal Teknologi Pertanian, 2001)
Alginate is a complex organic compound of phycocolloid, extracted from brown seaweeds. Â  The objective of this research was to obtain the best extraction procedure and to evaluate the characteristics of alginate produced from Padina sp.This research used a Block Random Design having two phases. The first phase had two factors, i.e HCl solution (0,5, 0,75, and 1%) and Â concentrations of Na2CO3 (2,5 5 and 7,5%). The best result of the combinations was used for the second research. The second phase also had two factors, they were Ca(OCl)2 as bleaching agent (0, 1 and 2%) and Â concentration of purification agent by using isopropanol (75, 85 and 95%). As the second Â parameters taken were yield, water content, ash, lightness, Pb and Hg content, viscosity and Â effect of pH and heating on the product.The result showed that there was a significant interaction of HCl and Na2CO3 concentration (ï¡ = 0,05) to the yield. But insignificant result were the viscosity and ash content. The concentration of HCl showed a significant effect to ash content. There was an interaction between HCl concentration Â and Na2CO3 to the yield, water content and viscosity. The concentration of Ca(OCl) 2 and isopropanol showed a significant effect to viscosity and water content, and showed an insignificant effect to lightness.Â The best treatment was the combination between HCl Â 1% and Na2CO3 5%, Â bleached by using Ca(OCl)2 2% Â and purified by using Â isopronanol 85%. They produced 30,30% of alginate salt, having parameters such as: viscosity of 12,2 cps, ash content of 30,51%, water content of 11,21% and lightness score of 53,89.The characteristics alginate produced from Padina sp. revealed having Hg content of Â 0,26 ppm and 6,15 ppm of Pb which is still below the limit of government regulation, and Â posess Â of decreasing of viscosity on extreme pH as well as heating treatments. Â By using infra red spectrum, Â the Â alginate Â produced Â in this experiment Â characterized into a Â Chemical group of C-C-C-C-C-C, Â -O-H. â€“COOH,C-O-C, and C-H.Key words : alginate, extraction, Â characterization